Tell her no lies [large type] - Irvin, Kelly (Center Point Large Print, 2019)
"Combining romance and suspense, Tell Her No Lies is a high-stakes race for the truth set in San Antonio. When Nina's uncle is murdered and the detective assigned to the case accuses Nina of the crime, she knows she must act using her journalism background to find the real killer"--